Comparative analysis of Klafki and Heimann’s didactic models - Bojović, Žana P.; Purić, Daliborka S. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
A comparative analysis of Klafki’s didactic thinking which is based on an analysis of different kinds of theories on the nature of education and Heimann’s didactic which is based on the theory of teaching and learning shows that both are dealing with teaching in its entirety. Both authors emphasize the role of contents, methods, procedures and resources for material and formal education and both use anthropological and social reality as their starting point. According to Klafki, resources, procedures, and methods are in form of dependency where it is important to know what and why should something be learnt, whereas Heimann sees the same elements in the form of interdependency. Each of the didactic conceptions, from their point of view, define the position of goals and tasks in education as well as how to achieve them. Determination and formulation of objectives is a complex, responsible, and very difficult task, and a goal must be clearly defined, because it emanates the guidelines for the preparation of didactic methodology educational programs and their planning. The selection of content in didactic methodology scenarios of education and learning, are only possible if the knowledge, skills and abilities that are necessary for a student to develop are explicitly indicated. The question of educational goals is the main problem of didactics for only a clearly defined objective implicates the selection of appropriate methods and means for its achievement, and it should be a permanent task of the current didactic conception now and in the future.